2019
DOI: 10.1093/nar/gkz482
|View full text |Cite
|
Sign up to set email alerts
|

A distal enhancer maintaining Hoxa1 expression orchestrates retinoic acid-induced early ESCs differentiation

Abstract: Retinoic acid (RA) induces rapid differentiation of embryonic stem cells (ESCs), partly by activating expression of the transcription factor Hoxa1, which regulates downstream target genes that promote ESCs differentiation. However, mechanisms of RA-induced Hoxa1 expression and ESCs early differentiation remain largely unknown. Here, we identify a distal enhancer interacting with the Hoxa1 locus through a long-range chromatin loop. Enhancer deletion significantly inhibited expression of RA-induced Hoxa1 and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 80 publications
0
47
0
Order By: Relevance
“…Specifically, long-range loops were diminished, and were replaced by compensatory interactions with regions of the SKAP2 gene. Some of these candidate enhancers have been reported in other studies (32), but have not previously been shown to be active in hematopoietic cells. Further investigation of these sequences, and their associated regulatory proteins, may shed light into factors that promote HOXA gene activation in normal and malignant myeloid cells.…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, long-range loops were diminished, and were replaced by compensatory interactions with regions of the SKAP2 gene. Some of these candidate enhancers have been reported in other studies (32), but have not previously been shown to be active in hematopoietic cells. Further investigation of these sequences, and their associated regulatory proteins, may shed light into factors that promote HOXA gene activation in normal and malignant myeloid cells.…”
Section: Discussionmentioning
confidence: 89%
“…To investigate whether CBE +47 has a regulatory effect, CRISPR-Cas9 mediated deletion method was used for further research ( Su et al, 2019 ). Two sgRNAs were designed in upstream and downstream of CBE +47 ( Figure 2A ), after Cas9 cleavage and DNA recombination, we obtained two homozygous CBE +47 knockout cell lines (CBE +47 -KO).…”
Section: Resultsmentioning
confidence: 99%
“…Studies by us and others have found that there are three enhancers at the 3’-end of HoxA ( Figure 5A ). The three enhancers (e.g., E1, E2 and E3) are required for HoxA expression during RA-induced ESC differentiation ( Cao et al, 2017; Liu et al, 2016; Su et al, 2019; Yin et al, 2015 ). Among them, it has been reported that E1 and E3 have significant long-range interactions with HoxA chromatin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations